Does eCG improve conception rate in Ongole (Bos indicus) ET recipient cows? - A Field Study - Kurati, Sunny Praveen; Nistala, Raghavendra Srikanth; Murakonda, Mutha Rao (The Indian Journal of Animal Reproduction, 2026)
Embryo transfer (ET) efficiency in cattle depends not only on embryo quality but also on recipient receptivity. This study evaluated the effect of equine chorionic gonadotropin (eCG) on estrus response, luteal development and conception rates in Ongole (Bos indicus) cows used as ET recipients, while also comparing conception rates between fresh and frozen embryo transfers. 53 reproductively sound Ongole cows were randomly assigned to Group 1 (with eCG, n=16) and Group 2 (without eCG, n=37) and synchronized using a progesterone-based protocol. Results revealed that the estrus response was similar between the two groups (88% vs. 84%), but eCG -treated cows exhibited more pronounced vulvar edema and cervico-vaginal mucus and higher corpus luteum (CL) development (56.25% vs. 35%), including multiple CLs observed exclusively in stimulated cows. Despite these physiological variations, conception rates remained compa rable across treatments, with no significant differences observed between eCG-treated and untreated cows (6.25% vs. 19%), between fresh embryos transferred with or without eCG (9.09% vs. 25%), or between frozen embryos transferred with or without eCG (0.00% vs. 7.69%). All conceived animals delivered viable calves. These results indicate that while eCG enhances luteal activity and estrus detectability in Ongole recipients, it does not significantly improve pregnancy outcomes, suggesting its use should be targeted rather than routine in ET programs.
Keywords: Conception rate; Corpus luteum; Embryo transfer; Estrus response; Equine chorionic gonadotropin (eCG); Ongole cows